2020
DOI: 10.3390/brainsci10100701
|View full text |Cite
|
Sign up to set email alerts
|

Association between Chronic Pain and Alterations in the Mesolimbic Dopaminergic System

Abstract: Chronic pain (pain lasting for >3 months) decreases patient quality of life and even occupational abilities. It can be controlled by treatment, but often persists even after management. To properly control pain, its underlying mechanisms must be determined. This review outlines the role of the mesolimbic dopaminergic system in chronic pain. The mesolimbic system, a neural circuit, delivers dopamine from the ventral tegmental area to neural structures such as the nucleus accumbens, prefrontal cortex, anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 108 publications
0
45
0
Order By: Relevance
“…Activity of ACC neurons is necessary and sufficient for the coding and processing of pain and the accompanying emotional pain, and the balance between neural excitation and inhibition is necessary for the normal function of the ACC ( Gong et al, 2010 ; Zugaib et al, 2014 ). In chronic pain clinical practice and basic research, changes in neurotransmitters in the central system have been found, which was caused by the dysregulation of GABAergic, glutamatergic, dopaminergic and opioidergic mechanisms ( Mhalla et al, 2010 ; Bannister and Dickenson, 2020 ; Yang et al, 2020 ). Dysfunction of GABAergic interneurons, as a major inhibitory system in the central nervous system, was reported to be closely related to the pathogenesis of anxiety-like behavior and chronic pain ( Möhler, 2012 ; Lau and Vaughan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Activity of ACC neurons is necessary and sufficient for the coding and processing of pain and the accompanying emotional pain, and the balance between neural excitation and inhibition is necessary for the normal function of the ACC ( Gong et al, 2010 ; Zugaib et al, 2014 ). In chronic pain clinical practice and basic research, changes in neurotransmitters in the central system have been found, which was caused by the dysregulation of GABAergic, glutamatergic, dopaminergic and opioidergic mechanisms ( Mhalla et al, 2010 ; Bannister and Dickenson, 2020 ; Yang et al, 2020 ). Dysfunction of GABAergic interneurons, as a major inhibitory system in the central nervous system, was reported to be closely related to the pathogenesis of anxiety-like behavior and chronic pain ( Möhler, 2012 ; Lau and Vaughan, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, DA is considered as anti-nociceptive and persistent pain is often associated with a decreased DA levels in brain as opposed to acute pain, such as a pin prick. [55][56][57][58] Therefore, a significantly increased DA and its degradation products observed in the striatum and pre-frontal cortex could be potentially attributed to a pathway that directly alters DA metabolism, such as p-cresol mediated inhibition of DBH. Increased DA (or its degradation products) to norepinephrine ratio as seen in both striatum and pre-frontal cortex of the C. difficile infected mice has been implicated in disorders of DBH activity, such as low DBH levels due to mutations in DBH coding genes.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways involved in sensory processing modulate pain [ 5 ]. These pathways are altered across the “on” and “off” states in PD, and an alteration of the pathways is closely related to pain processing in the brain [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…These pathways are altered across the “on” and “off” states in PD, and an alteration of the pathways is closely related to pain processing in the brain [ 6 , 7 , 8 ]. The mesolimbic pathway is associated with reward and motivation and plays an important role in the perception and modulation of pain [ 5 ]. The nucleus accumbens (NAc) is a central component of the mesolimbic pathway and is connected to pain-related brain regions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%